Arsenic exposure associated with decreased bone mineralization in male. (December 2014) - Akbal, Ayla; Yılmaz, Hınç; Tutkun, Engin
Abstract Objective: Arsenic (As) exposure may cause several medical problems. There were a few studies investigated whether it has affected bone tissue in women. However, there was no study in men. The aim of this study was to evaluate associations between bone mineral density (BMD) and As exposure in men subjects. Material and methods: We enrolled in this study 254 subjects who due to chronic As exposure suspected and 82 subjects as a control group. Hair As levels were detected by a hair analysis (Varian AA240Z Zeeman Atomic Absorption Spectrometer, USA). BMD measurements were obtained using dual-energy X-ray absorptiometry instrumentation. We investigated associations between the hair As levels and BMD measurements. Results: The frequency of osteoporosis and osteopenia was found to be 0.8% and 54.5%, respectively, in the As exposure group. The frequency of osteoporosis was found to be 1% and osteopenia was 32.4% in control subjects. There was significant difference between two groups (p < 0.001). Hair As level has a median 1.01 (min: 0.06 and max: 25.71). There were no significant correlation between hair As levels and BMD measurements. Conclusion: According to our observations, As exposure was associated with bone metabolism. Possible cause of osteopenia may be exposure to As. Further investigations are needed to estimate the relationship between As and bone metabolism.